Proceedings of 1993 2nd IEEE International Workshop on Robot and Human Communication
DOI: 10.1109/roman.1993.367695
|View full text |Cite
|
Sign up to set email alerts
|

Emotional evaluation of human arm motion models

Abstract: Emotional evaluation of human arm motion models is considered by the use of semantic differential test. The models are determined by changing the velocity pattern. The human arm motion model is recreated by CRT display and by an industry robot.In order to verify the influence of the smoothness of the velocity peak position to human motions. the robot hand motions whose velocity are based on the human results and the robot hand motions whose velocity are approximated by a triangle are conducted. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…On the other hand, physical movements hold great importance for the emotional interaction between humans and products and can be used as a tool for expressing emotions. Research proves that velocity contributes a lot in motion of robot to develop human-likeness [31]. Moreover, in human-robot interaction safety and comfort are important factors that are linked with velocity and acceleration, respectively [32].…”
Section: Modeling Machine Emotionsmentioning
confidence: 99%
“…On the other hand, physical movements hold great importance for the emotional interaction between humans and products and can be used as a tool for expressing emotions. Research proves that velocity contributes a lot in motion of robot to develop human-likeness [31]. Moreover, in human-robot interaction safety and comfort are important factors that are linked with velocity and acceleration, respectively [32].…”
Section: Modeling Machine Emotionsmentioning
confidence: 99%
“…Human subjects watched the simulations displayed on a computer CRT and evaluated their motions. The indicated fusion exercises were inspected with the method conformed to rating scale method used for the psychological evaluations of robot motions [8]- [10]. Here, we used five adjectives (smooth -awkward, fast -slow, careful -careless, skilled -unskilled, and human likeun-human like'').…”
Section: B Evaluationmentioning
confidence: 99%
“…Shibata et a1. [14] evaluated human emotions to the robot motions under various velocity patterns using semantic differential method. It was confirmed that human emotions to the robot motions change with velocity profile, velocity peak position in the duration, and maximum velocity.…”
Section: Introductionmentioning
confidence: 99%